The Effect of Red Betel Leaf Decoction on the Degree of Vaginal Discharge in Adolescents at the Pondok Pesantren Martausshibyan, Cianjur Regency, Indonesia - Risa Puspita Martin; Tia Suciati (Archives of The Medicine and Case Reports, 2023)
Vaginal discharge is an unusual discharge other than blood from the vaginal canal, whether it smells or not, accompanied by itching or not in the local area. This study aimed to determine the effect of boiled red betel leaves on the degree of vaginal discharge in teenagers at the Pondok Pesantren Martausshibyan, Cianjur Regency, Indonesia. This research design uses a one-group pretest-posttest experimental research design with a paired t-test with 30 respondents who carried out 2 measurements, namely measurements during the pre-test and measurements during the post-test. The results showed that there was a decrease in the degree of vaginal discharge before and after the intervention (2.23 Â± 0.11 Vs 1.13 Â± 0.12) with p <0.05. In conclusion, there is an effect of giving boiled water from red betel leaves on the degree of vaginal discharge of adolescents at the Pondok Pesantren Martausshibyan, Cianjur Regency, Indonesia.